SOCIAL MEDIA-BASED ACADEMIC WRITING INSTRUCTION IN INDONESIAN HIGHER EDUCATION INSTITUTIONS - Yanti Juniarti; Ayu Octarina; Armi Antasari (INJOSEDU: International Journal of Social and Education, 2026)
The development of digital technology and social media has brought significant changes to the learning process in higher education, including in academic writing. This study aims to analyze the implementation of social media-based academic writing learning in higher education institutions in Indonesia through a literature review approach. The research method used is a literature study by reviewing various scientific articles, national and international journals, proceedings, and relevant academic sources that discuss the use of social media in academic writing learning in higher education environments. The results of the study indicate that the use of social media platforms such as WhatsApp, Instagram, YouTube, Facebook, and Google Classroom can improve academic interaction, student collaboration, writing creativity, and learning motivation in the academic writing process. Social media also provides easy access to learning resources, rapid feedback, and learning flexibility that support the development of students' scientific writing skills. In addition, the use of social media in academic writing learning is considered effective in creating a more participatory and communicative learning environment. However, several challenges are faced, such as distractions from social media use, low academic digital literacy, and the potential for plagiarism in the writing process. This study concludes that social media-based academic writing learning has significant potential to improve the quality of academic writing instruction in Indonesian universities if supported by appropriate pedagogical strategies, strong academic supervision, and ongoing technology integration. This research is expected to serve as a reference for academics and educational institutions in developing effective digital learning innovations that are adaptive to technological developments.